The diffusion of corporate social responsibility through social network ties: From the perspective of strategic imitation. (5th September 2018) - Zou, Hailiang; Xie, Xuemei; Meng, Xiaohua; Yang, Mengyu
Abstract: Drawing on institutional and organizational learning theories, this study empirically investigates the imitation of corporate social responsibility (CSR) between firms tied by board interlocks, an important type of corporate social network tie. We propose a positive relationship between the CSR engagement of a focal firm and that of its tied‐to partners and examine how this relationship is moderated by the characteristics of both the focal and tied‐to firms. Using a sample of Chinese‐listed companies, empirical evidence is provided to show that a firm's engagement in symbolic CSR is in a positive relationship with that of its tied‐to partners; this relationship becomes stronger for smaller firms and those facing high uncertainty. Furthermore, when firms are linked to smaller firms, this relationship becomes more prominent. Our findings contribute to the CSR and social network literature, as well as the research on strategic imitation. Finally, implications for business management and government policy are discussed.